Merging Engineering Education with Service-Learning: How Community Based Projects Encourage Socially Conscious Engineers - Aaron Brown; Michael Bauer (Athens Institute for Education and Research, 2020)
Engineers provide essential services to society, solving pressing challenges through technological inventiveness. Students new to engineering often cite the lure of creative problem solving as attracting them to the discipline. However, traditional engineering curricula typically focus on a narrow application of fundamentals for solving closed-ended problems. Too often, engineering programs do not encourage inventive expression in problem solving. Not surprisingly, the attrition rate for engineering programs is unusually high. Recently, engineering education has shifted its focus to new, more engaging practices that incorporate hands-on methods, boosting prospects for students to engage in creative problem solving. Because service learning provides opportunities for applied work, incorporating it into engineering education programs in can engage students positively and lower attrition rates. Moreover, since engineers are fundamentally involved with social improvement, then engaging students in activities that expand their understanding of the potential impact their skills may impart to a community is not only prudent but best practices. This paper explores two case studies of community-based service learning engineering projects, highlighting community partnerships, analyses and decision-making that helped drive designs and outcomes. It explores how both the communities and students benefitted, focusing notably on the influence these activities had on student understanding of their work, academic and/or professional direction and social consciousness. These are analyzed via longitudinal reporting of students incorporating lessons learned several years post-project. The service learning projects took place in marginalized communities in Denver and Costa Rica. In the Denver project, engineering students designed, built and installed low cost solar heaters into an area with poor housing stock. In Costa Rica, students built a solar water heater for a local school.